Annie Oakley - Gleiter, Jan; Thompson, Kathleen; Miyake, Yoshi (Austin, TX : Raintree/Steck, 1995)
Presents the life of Annie Oakley who became a sharp shooter as a child and later starred in Buffalo Bill's Wild West Show.
1-3.
3.
Keywords: Oakley, Annie, -- 1860-1926; Entertainers -- Biography; Women -- Biography